Internal Party Democracy and Institutionalization of Political Parties in Nigeria’s Fourth Republic - Innocent, Alfa Patrick; Eikojonwa, Otaida; Yusoff , Kamarul Zaman Haji (South Asian Journal of Social Sciences and Humanities, 2020)
This paper interrogates the connection between the level of internal party democracy which exists in Nigeria’s Fourth Republic political parties and their propensity to become institutionalised. The objective is to unravel the reason for their inability to make effective contribution the deepening of democracy in the country. The paper is descriptive and conceptual. It got insights from secondary data which includes journal articles, national dailies, internet, magazines and textbooks. The data gathered were analysed under various themes. The paper contends that Nigeria’s Fourth Republic political parties do not adhere to the tenets of internal party democracy, thus undermining the prospects of their institutionalisation and negates the performance of their democratic functions. The paper offers valuable suggestions that could enhance the level of internal party democracy in the parties, propel them towards institutionalisation and most fundamentally contribute optimally to the consolidation of democracy in the Fourth Republic and beyond.